1997
DOI: 10.1165/ajrcmb.17.3.2737
|View full text |Cite
|
Sign up to set email alerts
|

Protein Cross-linking Mediated by Tissue Transglutaminase Correlates with the Maturation of Extracellular Matrices During Lung Development

Abstract: At birth, the mammalian lung is still immature. The alveoli are not yet formed and the interairspace walls contain two capillary layers which are separated by an interstitial core. After alveolarization (first 2 postnatal weeks in rats) the alveolar septa mature: their capillary layers merge, the amount of connective tissue decreases, and the mature lung parenchyma is formed (second and third week). During the first 3 wk of life the role of tissue transglutaminase (tTG) was studied in rat lung by immunostainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Reber-Müller et al (1995, 1996) suggested this possibility, although Schmid et al (1999) suggested that the microfibrils alone were responsible for the observed elasticity of the fibres. It seems more likely that the functionally continuous model is correct, particularly given the high volume fraction and high degree of overlap of the microfibrils in the fibre and observations by several authors of irreversible transglutaminase-derived crosslinks between fibrillin-rich microfibrils in several systems (Thurmond and Trotter, 1996;Qian and Granville, 1997;Schittny et al, 1997;Kielty et al, 2002). In either case, however, we conclude that the modulus of the microfibrils must be much less than the 78-96·MPa reported by Sherratt et al (2003) and that it should be of the order of 1·MPa.…”
Section: Case 4 Discontinuous and 1·mpamentioning
confidence: 97%
“…Reber-Müller et al (1995, 1996) suggested this possibility, although Schmid et al (1999) suggested that the microfibrils alone were responsible for the observed elasticity of the fibres. It seems more likely that the functionally continuous model is correct, particularly given the high volume fraction and high degree of overlap of the microfibrils in the fibre and observations by several authors of irreversible transglutaminase-derived crosslinks between fibrillin-rich microfibrils in several systems (Thurmond and Trotter, 1996;Qian and Granville, 1997;Schittny et al, 1997;Kielty et al, 2002). In either case, however, we conclude that the modulus of the microfibrils must be much less than the 78-96·MPa reported by Sherratt et al (2003) and that it should be of the order of 1·MPa.…”
Section: Case 4 Discontinuous and 1·mpamentioning
confidence: 97%
“…Transglutaminases catalyze the formation of an isopeptide ␥-glutamyl-⑀-lysine bond either between or within polypeptide chains. Tissue transglutaminase (tTG, TG-2, TG C ) is important in stabilizing developing extracellular matrices including lung and bone and in wound repair (30,31). The cross-link site on fibrillin-1 was localized to three glutamines within the fibrillin-1 TB2 domain (exon 17), which are on the domain surface.…”
Section: Fibrillin-1 Interactions With Tropoelastin and Magp-1mentioning
confidence: 99%
“…The first two components have been previously described in detail elsewhere [61,62,84,85] and thus are only recapitulated briefly here. The em-phasis of the present work is on the third component; the experimental methods are described in detail below.…”
Section: Methodsmentioning
confidence: 99%